Advances in information and computer security : 10th International Workshop on Security, IWSEC 2015, Nara, Japan, August 26-28, 2015, Proceedings /: 10th International Workshop on Security, IWSEC 2015, Nara, Japan, August 26-28, 2015, Proceedings. (2015) - Unknown
No abstract available